Writing against history, in the Novel Without a Name and The Disappeared - Jabarouti, Roya; Mani, Manimangai (2014)
It raises a lot of questions when entirely fictional stories occur in real settings and situations. While Duong Thu Huong, the author of the Novel Without a Name (1995), explores central jungles of Vietnam towards the end of the war, Kim Echlin, the author of The Disappeared (2009) takes the reader to wander around in the post-genocide streets of Cambodia. Nevertheless, what they illustrate is not the official history, but the private memories of the past. This study examines each novel for their emphasis on remembering the past versus re-constructing the history in their settings. This analysis, also indicates the ways through which fiction can help relive in the reality of the past, and, hence, avoid its prepetition in the future.